Getting started with Tableau 2018. x : get up and running with the new features of Tableau 2018 for impactful data visualization - Guillevin, Tristan (Packt Publishing Ltd, 2018)
Tableau is one of the leading data visualization tools and regularly adds new functionalities to the product. This book will help you understand these new features with clear examples, and is also an excellent beginner's guide to start using Tableau in the most efficient way.